College Writing Skills - Langan John (MC Graw Hill, 2005)
This text might also be useful for high school English courses. The only reason I don't give it 5 stars is because some of the grammar/punctuation sections don't have quite enough exercises in them to help some lower-level students get a firm grasp on the ideas. However, any teacher well-armed with worksheets can remedy that problem immediately!